Self-adsorption-resistant iron-based catalyst as well as preparation method and application thereof

By preparing anti-self-adsorption type iron-based catalysts, using small-size Fe3O4 nanocluster materials and organic acid modification, the problems of slow conversion speed and agglomeration effect of iron-based catalysts were solved, and the effect of efficient degradation of rhodamine B was achieved, and good industrial prospects were demonstrated.

CN119771509AInactive Publication Date: 2025-04-08CHINA WEST NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510093993.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The conversion of existing iron-based catalysts from Fe(II) to Fe(II), leads to a low reaction rate, and large-sized materials will produce agglomeration effect over time to reduce the reaction rate.

Method used

Using the preparation method of anti-self-adsorption iron-based catalyst, small-sized Fe3O4 nanocluster material was obtained by synthesizing oily precursors, ultra-small iron tetraoxide nanoclusters (USIONC) and organic acid modification, which increased the reactive site and reduced the self-adsorption effect.

Benefits of technology

The circulation speed between Fe(III) and Fe(II) is improved, the reaction rate is increased, the efficiency of degrading rhodamine B can reach 98%, and the catalyst has super paramagnetic and good dispersion, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771509A_ABST
    Figure CN119771509A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-self-adsorption iron-based catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalysts. According to the organic acid modified small-size self-adsorption-resistant iron-based catalyst provided by the invention, the reaction active sites are increased through the high specific surface area brought by size reduction, and the catalyst shows superparamagnetism, shows good dispersity in the absence of a magnetic field and reduces the self-adsorption effect of a material. The invention further provides a preparation method of the catalyst, BMPA-USIONC is obtained by synthesizing an oily precursor, synthesizing USIONC and treating USIONC with 2-bromoisobutyric acid, and the method is simple and easy to implement and low in input cost and has excellent industrial prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to an anti-self-adsorption type iron-based catalyst and a preparation method and application thereof. Background Art

[0002] Rhodamine B (RhB) is a common red cationic alkaline dye that is widely used in dyeing processes such as textiles, leather and paper. However, the irregular wastewater discharge of many factories has caused RhB to flow into water bodies. Due to its high chromaticity, difficulty in degradation, high concentration and high toxicity, it has become one of the main pollutants in water bodies and has seriously threatened the living environment of humans and animals. Textile dyes have been identified as non-biodegradable organic pollutants, and traditional methods have been proven to be ineffective and will cause secondary pollution. What is more serious is that dyes are generally hydrophobic and easily combine with nanomaterials in the environment to increase their toxicity. Therefore, it is urgent to provide an efficient and green degradation method to remove dye pollutants in wastewater.

[0003] As a mainstream method for removing pollutants from water bodies, advanced oxidation technology (AOP) based on peroxymonosulfate (PMS) has been proven to have a good degradation effect on dye pollutants and can significantly reduce the concentration of dye pollutants in a relatively short period of time. Its mechanism of action is to provide additional energy required by transition metals, ultrasound, microwave assistance, ultraviolet light irradiation, thermal activation, electrolysis, etc., and produce hydroxyl radicals (-OH) and other reactive oxygen species (ROS), such as SO4, under the action of PMS. - , O2 - , 1 O2, HO2 - etc., to mineralize pollutants and decompose non-toxic and harmless products such as carbon dioxide, water and inorganic salt ions, thereby achieving the purpose of pollutant degradation. Among the many materials used in AOP, iron-based transition metal materials are widely used in wastewater treatment due to their non-toxicity, high economic benefits and environmental friendliness. For example, the degradation rate of methyl orange dye and Congo red dye can reach 85%, 89.6%, etc. However, when using iron-based materials for reactions, the conversion of Fe(III) to Fe(II) is slow, resulting in a slower Fenton-like reaction rate. In addition, large-sized iron-based materials will produce their own agglomeration over time, which will also slow down the reaction rate. Summary of the invention

[0004] In view of the above-mentioned prior art, the present invention provides an anti-self-adsorption type iron-based catalyst and its preparation method and application, which solves the problem of slow conversion of Fe(III) to Fe(II) and low reaction rate.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing an anti-self-adsorption type iron-based catalyst, comprising the following steps:

[0006] S1: adding a mixture of ferric chloride hexahydrate and sodium oleate to a mixture of ethanol, water and n-hexane, ultrasonicating at 30-40 kHz for 10-15 min, heating and refluxing at 65-75° C. for 4 h, cooling the solution to room temperature, separating the oil layer, washing the oil layer, and drying the oil layer to constant weight to obtain an oily precursor;

[0007] S2: Add the oily precursor to a mixture of oleic acid, oleyl alcohol and diphenyl ether, and perform ultrasound at 30-40 kHz until the oily precursor is dissolved. Then, heat the mixture to 80-100°C in an inert gas environment and keep the temperature for 2 hours. After the temperature is kept, heat the mixture to 250°C at a rate of 10°C / min and keep the temperature for 30 minutes. After the temperature is kept, cool the mixture to room temperature, add acetone to the mixed solution, wash the precipitate, and dry it to constant weight to obtain ultrasmall ferroferric oxide nanoclusters.

[0008] S3: Ultra-small ferroferric oxide nanoclusters are dissolved in distilled water, and 2-bromoisobutyric acid is added to obtain a mixed solution 1, which is dispersed in a mixed solution of DMF and CHCl3, and then heated in an oil bath at 80°C and stirred for 12 hours to obtain an anti-self-adsorption iron-based catalyst.

[0009] The beneficial effects of the present invention are as follows: compared with the common nanoassembly idea, the present invention solves its own problems from the perspective of size and relies on the size-dependent performance of Fe3O4 itself. The present invention synthesizes an oily precursor, synthesizes USIONC, and uses 2-bromoisobutyric acid to treat USIONC. The anti-self-adsorption type iron-based catalyst obtained belongs to a small-sized Fe3O4 nanocluster material. The high specific surface area brought about by the size reduction increases the reaction active sites, and it will show superparamagnetism. It shows good dispersibility in the absence of a magnetic field and reduces the self-adsorption of the material. At the same time, organic acid modification can accelerate the circulation between Fe(III) and Fe(II) and increase the reaction rate. Moreover, the method is simple and easy to implement, has low investment cost, and has excellent industrial prospects.

[0010] Based on the above technical solution, the present invention can also be improved as follows.

[0011] Furthermore, the mass ratio of ferric chloride hexahydrate to sodium oleate is 1:3-4.

[0012] Furthermore, the volume ratio of ethanol, water and n-hexane is 4:3:7.

[0013] Furthermore, the mass ratio of oleic acid, oleyl alcohol and diphenyl ether is 1:3.2:20.

[0014] Furthermore, the mass ratio of the oily precursor to the mixed liquid of oleic acid, oleyl alcohol and diphenyl ether is 1:6-7.

[0015] Furthermore, the material-liquid ratio of ultrasmall ferroferric oxide nanoclusters to distilled water in S3 is 80-90 mg:1 mL, and the mass ratio of the crude product to 2-bromoisobutyric acid is 1:19.

[0016] Furthermore, the volume ratio of DMF to CHCl3 is 1:1, and the volume ratio of the mixed solution 1 to the mixed solution of DMF and CHCl3 is 1:50.

[0017] Furthermore, the drying temperature of S1 and S2 is 55-65°C.

[0018] The invention also discloses a method for preparing the anti-self-adsorption type iron-based catalyst and an anti-self-adsorption type iron-based catalyst prepared by the method.

[0019] The beneficial effects of the present invention are as follows: compared with the traditional large-size ferrosoferric oxide catalyst, the self-adsorption-resistant iron-based catalyst prepared by the present invention will not self-agglomerate over time and has more practical value; and the self-adsorption-resistant iron-based catalyst has been proved to be non-toxic to organisms through cell and hemolysis experiments.

[0020] The invention also discloses the application of the anti-self-adsorption type iron-based catalyst in the degradation of rhodamine B.

[0021] The beneficial effects of the present invention are as follows: the present invention is the first to use ultra-small iron-based nanocluster materials modified with organic acids as catalysts for application in the degradation field; the catalyst can activate PMS to rapidly degrade rhodamine B within three minutes, and the degradation efficiency can be as high as 98%. During the degradation, no additional operations such as ultraviolet rays, heating, and ultrasound are required, and only milligram-level catalysts and millimole-level PMS need to be added to efficiently degrade rhodamine B at normal temperature and pressure; and the anti-self-adsorption iron-based catalyst of the present invention can be recycled and still has efficient degradation capability after being recycled 5 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a graph showing the degradation effect of different concentrations of PMS activated by BMPA-USIONC-1 on Rhodamine B;

[0023] Figure 2 This is a graph showing the degradation effect of Rhodamine B by BMPA-USIONC-1 activated with PMS under different pH conditions;

[0024] Figure 3 This is the degradation effect diagram of Rhodamine B by BMPA-USIONC-1 and BMPA-Fe3O4 activated PMS;

[0025] Figure 4This is the degradation effect of activated PMS on Rhodamine B after BMPA-USIONC-1 and BMPA-Fe3O4 were placed for one month;

[0026] Figure 5 The degradation effect of activated PMS on Rhodamine B after BMPA-USIONC-1 and BMPA-Fe3O4 were placed for one month and one week;

[0027] Figure 6 The degradation effect of activated PMS on Rhodamine B after BMPA-USIONC-1 and BMPA-Fe3O4 were placed for one month and two weeks;

[0028] Figure 7 This is a diagram showing the effect of BMPA-USIONC-1 cell experiments;

[0029] Figure 8 This is a record of the hemolysis experiment of BMPA-USIONC-1;

[0030] Fig. 9 This is the effect diagram of the hemolysis experiment of BMPA-USIONC-1;

[0031] Fig.10 This is the cycle effect diagram of BMPA-USIONC-1;

[0032] Fig.11 This is the degradation effect diagram of different concentrations of Rhodamine B in actual dye wastewater activated by BMPA-USIONC-1;

[0033] Fig.12 TEM image of BMPA-USIONC-1;

[0034] Fig.13 is the EDS spectrum of BMPA-USIONC-1;

[0035] Fig.14 TEM ring diffraction analysis diagram of BMPA-USIONC-1;

[0036] Fig.15 FTIR images of samples before and after BMPA modification;

[0037] Fig.16 This is the full XPS spectrum of USIONC before and after BMPA modification;

[0038] Fig.17 Zeta potential diagram of USIONC before and after BMPA modification. DETAILED DESCRIPTION

[0039] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0040] Example 1

[0041] A method for preparing an anti-self-adsorption type iron-based catalyst comprises the following steps:

[0042] S1: Take a mixture of 2.7g of ferric chloride hexahydrate and 9.125g of sodium oleate and add it to a mixture of 125mL of ethanol, water and n-hexane (the volume ratio of ethanol, water and n-hexane is 4:3:7), and then heat and reflux at 70°C for 4h after ultrasonic treatment at 35KHz for 12min. After the solution is cooled to room temperature, separate the oil layer with a separatory funnel, wash the oil layer with ultrapure water once, and then put the oil layer into an oven at 60°C and dry it to constant weight to obtain an oily precursor;

[0043] S2: 36 g of the oily precursor was added to a mixture of 10.4 g of oleic acid, 32.2 g of oleyl alcohol and 200 g of diphenyl ether, and the mixture was ultrasonically treated at 35 kHz until the oily precursor was dissolved. The mixture was then heated to 90°C and kept warm for 2 h under a nitrogen environment. After the heat preservation, the mixture was heated to 250°C at a rate of 10°C / min and kept warm for 30 min. After the heat preservation, the mixture was cooled to room temperature. Acetone in an amount of 3 times the mass of the solvent of the mixed solution was added to the mixed solution. The precipitate was washed with ether and dried in an oven at 60°C to constant weight to obtain ultrasmall ferroferric oxide nanoclusters (USIONC).

[0044] S3: Dissolve USIONC in distilled water (the solid-liquid ratio of USIONC to distilled water is 88 mg:1 mL), take 100 μL and add 166.67 mg 2-bromoisobutyric acid to obtain a mixed solution 1, and disperse it in a mixed solution of 5 mL DMF and CHCl3 with a volume ratio of 1:1, then heat in an oil bath at 80°C and stir for 12 h to obtain the anti-self-adsorption iron-based catalyst BMPA-USIONC-1.

[0045] Example 2

[0046] A method for preparing an anti-self-adsorption type iron-based catalyst comprises the following steps:

[0047] S1: Take a mixture of 2.7g of ferric chloride hexahydrate and 8.1 of sodium oleate and add it to a mixture of 125mL of ethanol, water and n-hexane (the volume ratio of ethanol, water and n-hexane is 4:3:7), and then heat and reflux at 65°C for 4h after ultrasonic treatment at 30KHz for 15min. After the solution is cooled to room temperature, separate the oil layer with a separatory funnel, wash the oil layer with ultrapure water once, and then put the oil layer into an oven at 55°C and dry it to constant weight to obtain an oily precursor;

[0048] S2: 40.4 g of the oily precursor was added to a mixture of 10.4 g of oleic acid, 32.2 g of oleyl alcohol and 200 g of diphenyl ether, and the mixture was ultrasonically treated at 30 kHz until the oily precursor was dissolved. The mixture was then heated to 80°C and kept warm for 2 h under a nitrogen environment. After the heat preservation, the mixture was heated to 250°C at a rate of 10°C / min and kept warm for 30 min. After the heat preservation, the mixture was cooled to room temperature. Acetone in an amount of 3 times the mass of the solvent of the mixed solution was added to the mixed solution. The precipitate was washed with ether and dried in an oven at 55°C to constant weight to obtain ultrasmall ferroferric oxide nanoclusters (USIONC).

[0049] S3: Dissolve USIONC in distilled water (the solid-liquid ratio of USIONC to distilled water is 80 mg:1 mL), take 100 μL and add 152 mg 2-bromoisobutyric acid to obtain a mixed solution 1, and disperse it in a mixed solution of 5 mL DMF and CHCl3 with a volume ratio of 1:1, then heat in an oil bath at 80°C and stir for 12 h to obtain the anti-self-adsorption iron-based catalyst BMPA-USIONC-2.

[0050] Example 3

[0051] A method for preparing an anti-self-adsorption type iron-based catalyst comprises the following steps:

[0052] S1: Take a mixture of 2.7g of ferric chloride hexahydrate and 10.8g of sodium oleate and add it to a mixture of 125mL of ethanol, water and n-hexane (the volume ratio of ethanol, water and n-hexane is 4:3:7), and then heat and reflux at 75°C for 4h after ultrasonic treatment at 40KHz for 10min. After the solution is cooled to room temperature, separate the oil layer with a separatory funnel, wash the oil layer with ultrapure water once, and then put the oil layer into an oven at 65°C and dry it to constant weight to obtain an oily precursor;

[0053] S2: 34.7 g of the oily precursor was added to a mixture of 10.4 g of oleic acid, 32.2 g of oleyl alcohol and 200 g of diphenyl ether, and the mixture was ultrasonically treated at 40 kHz until the oily precursor was dissolved. The mixture was then heated to 100°C and kept warm for 2 h under a nitrogen environment. The mixture was heated to 250°C at a rate of 10°C / min and kept warm for 30 min after the heat preservation. The mixture was cooled to room temperature after the heat preservation. Acetone in an amount of 3 times the mass of the solvent of the mixture was added to the mixture. The precipitate was washed with ether and dried in an oven at 65°C to constant weight to obtain ultrasmall ferroferric oxide nanoclusters (USIONC).

[0054] S3: Dissolve USIONC in distilled water (the solid-liquid ratio of USIONC to distilled water is 90 mg:1 mL), take 100 μL and add 171 mg 2-bromoisobutyric acid to obtain a mixed solution, and disperse it in a mixed solution of 5 mL DMF and CHCl3 with a volume ratio of 1:1, then heat in an oil bath at 80°C and stir for 12 h to obtain the anti-self-adsorption iron-based catalyst BMPA-USIONC-3.

[0055] Comparative Example

[0056] A method for preparing an anti-self-adsorption type iron-based catalyst comprises the following steps:

[0057] S1: Add 2.4 g of ferric chloride hexahydrate and 0.98 g of ferrous chloride tetrahydrate into 10 mL of distilled water and stir until dissolved. Then heat in an oil bath to 80°C. After reacting for 30 min, add 5 mL of ammonia water. After reacting for another 30 min, add 0.5 mL of oleic acid. Keep at 85°C for 12 h. Wash the precipitate with ultrapure water and dry in an oven at 60°C until constant weight to obtain a crude product.

[0058] S2: The crude product was dissolved in distilled water (the ratio of crude product to distilled water was 88 mg:1 mL), 100 μL was taken and 166.67 mg of 2-bromoisobutyric acid was added to obtain a mixed solution 1, which was then heated in an oil bath at 80°C and stirred for 12 h to obtain the anti-self-adsorption iron-based catalyst BMPA-Fe3O4.

[0059] The anti-self-adsorption type iron-based catalysts prepared in Examples 1 to 3 have similar effects. The subsequent experimental examples use the anti-self-adsorption type iron-based catalyst BMPA-USIONC-1 prepared in Example 1.

[0060] Experimental Example 1

[0061] Rhodamine B degradation experiment 1: Control group: prepare an RhB solution with an initial concentration of 20 mg / L for standby use, weigh 0.012 g of peroxymonosulfate and dissolve it in 4 mL of water for standby use, take 2730 μL of distilled water into a centrifuge tube, add 120 μL of RhB solution, and then add 150 μL of PMS solution to make the concentration of PMS 2 mM; allow it to degrade for ten minutes, take out 400 uL at time points of 1 min, 3 min, 5 min, 8 min, and 10 min for UV detection; the degradation efficiency of RhB is 2%.

[0062] Experimental group: prepare a RhB solution with an initial concentration of 20 mg / L for standby use, weigh 0.012 g of peroxymonosulfate and dissolve it in 4 mL of water for standby use, take 2730 μL of distilled water into a centrifuge tube, add 120 μL of RhB solution, then add 150 μL of PMS solution to make the concentration of PMS 2 mM, then add 150 μL of BMPA-USIONC-1 solution with a concentration of 100 mg / L; allow it to degrade for ten minutes, take out 400 uL for UV detection at time points of 1 min, 3 min, 5 min, 8 min, and 10 min; the degradation efficiency of RhB is 98%.

[0063] The experimental results show that Fe-CNP in BMPA-USIONC-1 can activate PMS, produce reactive oxygen, and greatly improve the degradation efficiency.

[0064] Experimental Example 2

[0065] Rhodamine B degradation experiment 2: prepare an RhB solution with an initial concentration of 20 mg / L for standby use, weigh 0.0003 g of peroxymonosulfate and dissolve it in 4 mL of water for standby use, take 2580 μL of water into a centrifuge tube, add 120 μL of RhB solution, and then add 150 μL of PMS solution to make the concentration of PMS 0.5 mM; then add 150 uL of BMPA-USIONC-1 solution with a concentration of 100 mg / L; allow it to degrade for ten minutes, and take out 400 uL for UV detection at time points of 1 min, 3 min, 5 min, 8 min, and 10 min.

[0066] Three more experiments were conducted according to the above scheme, with the difference that the concentrations of PMS were 1mM, 2mM and 4mM respectively. The experimental results are as follows Figure 1 As shown in the figure, with the increase of PMS dosage, more free radicals can be provided to improve the degradation efficiency. However, excessive PMS may competitively capture hydroxyl radicals during the reaction and inhibit their oxidation of pollutants, thereby reducing the degradation efficiency.

[0067] Experimental Example 3

[0068] Rhodamine B degradation experiment 3: Prepare an RhB solution with an initial concentration of 20 mg / L for standby use, weigh 0.012 g of peroxymonosulfate and dissolve it in 4 mL of water for standby use, add 120 μL of RhB solution, and then add 150 μL of PMS solution to make the concentration of PMS 4 mM; then add 2580 uL of water to a centrifuge tube and adjust the pH of the solution to 3, and then add 150 uL of BMPA-USIONC-1 solution with a concentration of 100 mg / L; allow it to degrade for ten minutes, and take out 400 uL for UV detection at time points of 1 min, 3 min, 5 min, 8 min, and 10 min.

[0069] Four more experiments were conducted according to the above scheme, with the difference that the pH was adjusted to 5, 7, 9 and 11. The experimental results are as follows Figure 2 As shown, the degradation efficiency can reach the maximum under neutral conditions of pH 7.

[0070] Experimental Example 4

[0071] Rhodamine B degradation experiment 4: prepare an RhB solution with an initial concentration of 20 mg / L for standby use, weigh 0.012 g of peroxymonosulfate and dissolve it in 4 mL of water for standby use, add 120 μL of RhB solution, then add 150 μL of PMS solution to make the concentration of PMS 4 mM, then add 2580 μL of water to a centrifuge tube and adjust the pH of the solution to 7, then add 150 uL of BMPA-USIONC-1 solution with a concentration of 100 mg / L; allow it to degrade for ten minutes, and take out 400 uL for UV detection at time points of 1 min, 3 min, 5 min, 8 min, and 10 min.

[0072] Prepare a RhB solution with an initial concentration of 20 mg / L for standby use, weigh 0.012 g of peroxymonosulfate and dissolve it in 4 mL of water for standby use, add 120 μL of RhB solution, then add 150 μL of PMS solution to make the concentration of PMS 4 mM, then add 2580 μL of water to a centrifuge tube and adjust the pH of the solution to 7, then add 150 uL of BMPA-Fe3O4 solution with a concentration of 100 mg / L; allow it to degrade for ten minutes, and take out 400 uL for ultraviolet detection at time points of 1 min, 3 min, 5 min, 8 min, and 10 min.

[0073] The experimental results are as follows Figure 3 As shown, both BMPA-USIONC-1 of Example 1 and BMPA-Fe3O4 of the comparative example have good degradation effects on RhB, but BMPA-Fe3O4 has a faster degradation efficiency. However, the two materials are placed for one month and their degradation efficiency on RhB is investigated every other week. Figures 4 to 6 As shown in the figure, as time goes by, the degradation performance of BMPA-Fe3O4 for RhB gradually deteriorates. After one month, the degradation rate is reduced to 88.18%. However, BMPA-USIONC-1 still has a good degradation efficiency for RhB after being placed for one month. This is because the size of BMPA-Fe3O4 is about 15nm, and it has strong magnetism. If it is placed for a long time, the material will agglomerate itself, resulting in insufficient contact with pollutants, and thus the degradation effect decreases. However, the size of BMPA-USIONC-1 is about 5nm, and the material will not agglomerate itself, so it has a longer validity period and more stable degradation efficiency.

[0074] Experimental Example 5

[0075] Cell experiment: An appropriate amount of pancreatic cancer cell solution was redispersed in a 96-well microplate with a cell solution volume of 100 μL / well, and cultured at 37°C for about 48 hours until it was in the exponential growth phase. Then, the culture medium was removed, and 100 μL of culture medium containing different concentrations of BMPA-USIONC-1 (120, 150, 300, 450 and 600 μg / mL) was supplemented as the experimental group, and 100 μL of culture medium without BMPA-USIONC-1 was used as the control group for incubation for 24 hours. Subsequently, 60 μL of filtered MTT DMEM solution was added to each well at a final concentration of 0.5 mg / mL. After 2 hours, the solution was removed and 100 μL DMSO was added to each well. In the dark, shake at a low speed on a constant temperature shaker for 10 minutes. The absorbance value of each well was measured at 490 nm using an enzyme reader, and the cell survival rate was calculated by the following formula:

[0076]

[0077] The experimental results are as follows Figure 7 As shown, the cell survival rate reached 99% when the BMPA-USIONC-1 concentration was 120 μg / mL. Although the cell survival rate decreased slightly with the increase of the material concentration, it was still close to 90% even at a concentration of 600 μg / mL, indicating that it has no biological toxicity to cells.

[0078] Experimental Example 6

[0079] Hemolysis experiment: 50 μL of blood was drawn from adult males and females of different genders and placed in a blood collection tube filled with heparin to obtain human whole blood (mixed blood, mixed gender), and 10 times the amount of PBS was added and centrifuged and washed 3 times (3000 rpm, 5 min) to obtain human red blood cells, which were resuspended in 3 mL of PBS; next, 0.1 mL of RBCs solution was mixed with 0.4 mL of PBS solution containing BMPA-USIONC-1 and gently shaken (350 rpm) at 37°C for 30 min, and then the above mixture was centrifuged to collect the supernatant (2000 rpm, 5 min). Finally, the absorbance value of the supernatant at 410 nm was measured. RBCs incubated with pure PBS and water were used as negative and positive controls, respectively. All samples were prepared in triplicate at one time. The calculation formula for the hemolysis percentage is as follows:

[0080]

[0081] The experimental results are as follows Figures 8-9 As shown, no obvious hemolytic toxicity was shown within the selected material concentration range (0.1-1 mg / mL), which indicates that the material has good biocompatibility and is harmless to organisms.

[0082] Experimental Example 7

[0083] Cyclic experiment: Prepare a RhB solution with an initial concentration of 20 mg / L for standby use, weigh 0.012g of peroxymonosulfate and dissolve it in 4mL of water for standby use, add 120μL of RhB solution, and then add 150μL of PMS solution to make the concentration of PMS 2mM. Then add 2580μL of water to make the pH of the solution = 7, and then add 150μL of BMPA-USIONC-1 solution with a concentration of 100mg / L. After ten minutes of degradation, 400uL was taken out for UV detection at time points of 1min, 3min, 5min, 8min, and 10min. Since the material has good dispersibility in the solution, it is difficult to separate it from the reaction system after the reaction. Therefore, the amount of material added in each experiment is constant. The difference is that twice the pollutants and PMS were added in the second cycle experiment, and three times the pollutants and PMS were added in the third cycle. After five experiments, BMPA-USIONC-1 was almost not consumed. Fig.10 As shown, it still has good degradation performance, indicating that the material has good practicality and stability.

[0084] Experimental Example 8

[0085] Practical application experiment: The wastewater in this experiment was collected from a textile factory in Gaoping District, Nanchong City, Sichuan Province. After testing, no RhB was detected in the dye processing wastewater. In order to investigate the application performance of this method in actual samples, RhB solutions of different concentrations were prepared: 10mg / L, 20mg / L, 30mg / L, and 40mg / L. Weigh 0.012g of peroxymonosulfate and dissolve it in 4mL of water for standby use. Add 120μL of RhB solution and 150μL of PMS solution to make the concentration of PMS 2mM. Then add 2580μL of water to the centrifuge tube and adjust the pH of the solution to 7. Then add 150μL of BMPA-USIONC-1 solution with a concentration of 100mg / L. After ten minutes of degradation, take out 400uL for ultraviolet detection at time points of 1min, 3min, 5min, 8min, and 10min. The experimental results are as follows Fig.11 As shown, BMPA-USIONC-1 has a good degradation efficiency for wastewater with different concentrations of RhB, indicating that BMPA-USIONC can activate PMS for the degradation of actual wastewater.

[0086] Experimental Example 9

[0087] Characterization experiment: The size and morphology of the BMPA-USIONC-1 prepared in Example 1 were observed using a transmission electron microscope. The results are as follows: Figures 12-14 As shown, BMPA-USIONC-1 particles are evenly distributed ( Fig.12 ), which is a spherical particle with a size of 5nm; Fig.13 The Br element on the material eds map proves the successful modification of BMPA and the maintenance of the material morphology before and after modification; Fig.14 , the presence of ferrosoferric oxide in the material is illustrated by the exposed crystal planes: (440), (400), (311), and (220).

[0088] In order to further verify the successful modification of BMPA onto USIONC, FT-IR tests were performed, such as Fig.15 The absorption peak at 602cm-1 is the characteristic absorption peak of Fe-O, the absorption peaks at 864 and 1020cm-1 are the characteristic absorption peaks of Br, and the absorption peak at 3420cm-1 is the absorption peak of OH. The above results prove that BMPA has been successfully modified on USIONC; and the subsequent ZETA potential shows an increase in the potential after modification (the electron-withdrawing effect of Br) and the characteristic peaks of Fe, O, C, and Br shown in the X-ray electron energy spectrum (XPS) ( Figures 16-17 ), which also proved that BMPA was successfully modified onto USIONC.

[0089] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A method for preparing an anti-self-adsorption type iron-based catalyst, characterized in that: The following steps are involved: S1: adding a mixture of ferric chloride hexahydrate and sodium oleate to a mixture of ethanol, water and n-hexane, ultrasonicating at 30-40 kHz for 10-15 min, heating and refluxing at 65-75° C. for 4 h, cooling the solution to room temperature, separating the oil layer, washing the oil layer, and drying the oil layer to constant weight to obtain an oily precursor; S2: Add the oily precursor to a mixture of oleic acid, oleyl alcohol and diphenyl ether, and perform ultrasound at 30-40 kHz until the oily precursor is dissolved. Then, heat the mixture to 80-100°C in an inert gas environment and keep the temperature for 2 hours. After the temperature is kept, heat the mixture to 250°C at a rate of 10°C / min and keep the temperature for 30 minutes. After the temperature is kept, cool the mixture to room temperature, add acetone to the mixed solution, wash the precipitate, and dry it to constant weight to obtain ultrasmall ferroferric oxide nanoclusters. S3: Ultra-small ferroferric oxide nanoclusters are dissolved in distilled water, and 2-bromoisobutyric acid is added to obtain a mixed solution 1, which is dispersed in a mixed solution of DMF and CHCl3, and then heated in an oil bath at 80°C and stirred for 12 hours to obtain an anti-self-adsorption iron-based catalyst.

2. The method for preparing the self-adsorption resistant ferroferric oxide nanocluster material according to claim 1, characterized in that: The mass ratio of the ferric chloride hexahydrate to sodium oleate is 1:3-4.

3. The method for preparing the anti-self-adsorption type iron-based catalyst according to claim 1, characterized in that: The volume ratio of the ethanol, water and n-hexane is 4:3:

7.

4. The method for preparing the anti-self-adsorption type iron-based catalyst according to claim 1, characterized in that: The mass ratio of oleic acid, oleyl alcohol and diphenyl ether is 1:3.2:

20.

5. The method for preparing the anti-self-adsorption type iron-based catalyst according to claim 1, characterized in that: The mass ratio of the oily precursor to the mixed liquid of oleic acid, oleyl alcohol and diphenyl ether is 1:6-7.

6. The method for preparing the anti-self-adsorption type iron-based catalyst according to claim 1, characterized in that: The material-liquid ratio of the ultrasmall ferroferric oxide nanoclusters to distilled water in the S3 is 80-90 mg:1 mL, and the mass ratio of the crude product to 2-bromoisobutyric acid is 1:

19.

7. The method for preparing the anti-self-adsorption type iron-based catalyst according to claim 1, characterized in that: The volume ratio of DMF to CHCl3 is 1:1, and the volume ratio of the mixed solution 1 to the mixed solution of DMF and CHCl3 is 1:

50.

8. The method for preparing the anti-self-adsorption type iron-based catalyst according to claim 1, characterized in that: The drying temperatures of S1 and S2 are both 55-65°C.

9. An anti-self-adsorption type iron-based catalyst obtained by the method for preparing an anti-self-adsorption type iron-based catalyst according to any one of claims 1 to 8.

10. Use of the anti-self-adsorption iron-based catalyst according to claim 9 in the degradation of Rhodamine B.